Molecular Characterization of Aquaporin 1 and Aquaporin 3 from the Gills of the African Lungfish, Protopterus annectens, and Changes in Their Branchial mRNA Expression Levels and Protein Abundance during Three Phases of Aestivation - Chng, You R.; Ong, Jasmine L. Y.; Ching, Biyun; Chen, Xiu L.; Hiong, Kum C.; Wong, Wai P.; Chew, Shit F.; Lam, Siew H.; Ip, Yuen K. (Frontiers in Physiology, 2016)
African lungfishes can undergo long periods of aestivation on land during drought. During aestivation, lungfishes are confronted with desiccation and dehydration, and their gills become non-functional and covered with a thick layer of dried mucus. Aquaporins (Aqps) are a superfamily of integral membrane proteins which generally facilitate the permeation of water through plasma membranes. This study aimed to obtain the complete cDNA coding sequences of aqp1 and aqp3 from the gills of Protopterus annectens, and to determine their branchial mRNA and protein expression levels during the induction, maintenance and arousal phases of aestivation. Dendrogramic analyses of the deduced Aqp1 and Aqp3 amino acid sequences of P. annectens revealed their close relationships with those of Latimeria chalumnae and tetrapods. During the induction phase, there were significant decreases in the transcript levels of aqp1 and aqp3 in the gills of P. annectens, but the branchial Aqp1 and Aqp3 protein abundance remained unchanged. As changes in transcription may precede changes in translation, this could be regarded as an adaptive response to decrease the protein abundance of Aqp1 and Aqp3 in the subsequent maintenance phase of aestivation. As expected, the branchial transcript levels and protein abundance of aqp1/Aqp1 and aqp3/Aqp3 were significantly down-regulated during the maintenance phase, probably attributable to the shutdown of branchial functions and the cessation of volume regulation of branchial epithelial cells. Additionally, these changes could reduce the loss of water through branchial epithelial surfaces, supplementing the anti-desiccating property of the dried mucus. Upon arousal, it was essential for the lungfish to restore branchial functions. Indeed, the protein abundance of Aqp1 recovered partially, with complete recovery of mRNA expression level and protein abundance of Aqp3, in the gills of P. annectens. These results provide insights into how P. annectens regulates branchial Aqp expression to cope with desiccation and rehydration during different phases of aestivation.